Empowering Women and Youth through Bundled Climate-Smart Agriculture and Climate Information Services in Ethiopia - Tesfaye, Abonesh; Gondwe, Therese; Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Key messages: - Women's engagement in CBBP cooperatives ensures their empowerment to make decisions. - Initiating women-led CBBP requires a series of consultations that need to be conducted to benefit from women's engagement in small ruminant improvement. - Implications for the path forward include a continued emphasis on tailored training, increased support for women farmers in technology adaptability, climate resilience, and financial inclusion. - The approach not only contributes to gender equality but also enhances the community's overall productivity.